2004
DOI: 10.1016/j.ejcts.2004.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Does off-pump coronary artery bypass reduce the incidence of post-operative atrial fibrillation? A question revisited

Abstract: Atrial fibrillation (AF) is the most common post-operative complication in patients undergoing coronary artery bypass grafting, with an increased incidence associated with advancing age. This study aims to determine whether off-pump coronary artery bypass (OPCAB) reduces the incidence of AF in a generalized population (mean age <70 years). A meta-analysis was performed including all randomised and propensity score matched non-randomised studies published between 2001 and 2003 reporting a comparison between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 41 publications
1
33
0
2
Order By: Relevance
“…Because we could no find a significant difference in atrial fibrillation between BH and CA strategies for stable patients, it can be speculated that the severity of preoperative myocardial damage triggers the development of atrial fibrillation and BH surgery might have an influence on that. 32 Stroke rate and the incidence of acute renal failure were also significantly reduced in BH patients, although most of the BH operations were performed with CPB support. It might be speculated that a faster postoperative cardiac recovery and preserved pulsatility have a protective potential.…”
Section: Patients With Cardiogenic Shockmentioning
confidence: 96%
“…Because we could no find a significant difference in atrial fibrillation between BH and CA strategies for stable patients, it can be speculated that the severity of preoperative myocardial damage triggers the development of atrial fibrillation and BH surgery might have an influence on that. 32 Stroke rate and the incidence of acute renal failure were also significantly reduced in BH patients, although most of the BH operations were performed with CPB support. It might be speculated that a faster postoperative cardiac recovery and preserved pulsatility have a protective potential.…”
Section: Patients With Cardiogenic Shockmentioning
confidence: 96%
“…The presence of cerebrovascular accident in these patients causes a five-fold increase in the rate of in-hospital death 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, beating heart CABG has become widely used and many studies have indicated that this procedure may decrease the incidence of post-CABG AF [8,9,10,11]. However, the molecular mechanisms underlying the protective effect of beating heart surgery remains unclear.…”
Section: Introductionmentioning
confidence: 99%